Variable expression of a surface determinant during proliferation of Candida albicans. - Chaffin, W L (1988)
The surface expression of an antigenic determinant that is present in the cell wall of Candida albicans was investigated with monoclonal antibody 24 (MAb24), an immunoglobulin M MAb. The proportion of the cell population that expressed the epitope under different growing conditions was determined by indirect immunofluorescence microscopy. More than 90% of stationary-phase yeast cells of strain B311 grown at 28 degrees C expressed the antigen. Less than 50% of yeast cells grown exponentially at 28 degrees C or either growing or stationary-phase yeast cells cultivated at 37 degrees C expressed the epitope. Germ tubes, which were induced at 37 degrees C from stationary-phase yeast cells grown at 28 degrees C, expressed the determinant on the parent yeast but not the hyphal portion of the germ tube. The change in antigen expression by stationary-phase cells grown at 28 degrees C, when they resumed growth by bud formation, suggested that antigen expression was lost by cells in the inoculum prior to the first cell division. By using the same assay, strong positive reactions were observed in stationary-phase cultures of other isolates of C. albicans, C. guilliermondii, C. stellatoidea, and C. tropicalis, but not with isolates of C. krusei, C. parapsilosis, or Torulopsis glabrata. The identification of the antigenic determinant as a carbohydrate was based on three observations: (i) interaction with a mannan preparation from the same organism, (ii) sensitivity of the antigen to periodate but not proteases, and (iii) coincidence of the migration of antigen during electrophoresis with material which stained intensely with carbohydrate but not with protein reagents. These observations suggest that the expression of the antigenic determinant of MAb24 is dependent on the growth conditions, growth state, and morphology of the cell and that the topography of the cell surface is dynamic.